Photosymbiosis for Biomedical Applications - Chávez, Myra N.; Moellhoff, Nicholas; Schenck, Thilo L.; Egaña, José Tomás; Nickelsen, Jörg (Frontiers in Bioengineering and Biotechnology, 2020)
Without the sustained provision of adequate levels of oxygen by the cardiovascular system, the tissues of higher animals are incapable of maintaining normal metabolic activity, and hence cannot survive. The consequence of this evolutionarily suboptimal design is that humans are dependent on cardiovascular perfusion, and therefore highly susceptible to alterations in its normal function. However, hope may be at hand. ‘Photosynthetic strategies’, based on the recognition that photosynthesis is the source of all oxygen, offer a revolutionary and promising solution to pathologies related to tissue hypoxia. These approaches, which have been under development over the past 20 years, seek to harness photosynthetic microorganisms as a local and controllable source of oxygen to circumvent the need for blood perfusion to sustain tissue survival. To date, their applications extend from the in vitro creation of artificial human tissues to the photosynthetic maintenance of oxygen-deprived organs both in vivo and ex vivo, while their potential use in other medical approaches has just begun to be explored. This review provides an overview of the state of the art of photosynthetic technologies and its innovative applications, as well as an expert assessment of the major challenges and how they can be addressed.